PENGARUH PRAKTEK CORPORATE GOVERNANCE TERHADAP LAMANYA AUDIT DELAY - Nurul Hidayah; Raja Adri Satriawan Surya; Arumega Zarefar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study was aimed to examine and analize the effect of audit committee size, audit committee meeting, audit committee expertise, board size, and independent board of commissioners toward audit delay at manufacture companies listed on the Indonesia Stock Exchange (IDX) in 2011-2016. This study is empirical study with purposive sampling technique was used to collect sample. The data was obtained from the annual report of companies listed on the IDX in 2011-2016 which consisted of 498 companies. Multiple regression was use to analyze the data. The result of hypothesis testing showed that the audit committee size and audit committee expertise have a negative impact toward audit delay. Furthermore, audit committee meeting have a positive effect to audit delay. Meanwhile, the board size and independent board of commissioners has no effect toward audit delay.Keyword : audit committee size, audit committee meeting, audit committee expertise, board size, independent board of commissioners, audit delay.